Exploring the Anti-Inflammatory and Anti-NET Properties of Zidian Zhenxiao Granule in IgA Vasculitis: A Network Pharmacology and Proteomic Study - Zhang X; Yang M; Duan X; Feng X; Fang Y (Journal of Inflammation Research, 2025)
Xiaofang Zhang,1 Minghang Yang,1 Xiaozheng Duan,1 Xiaochun Feng,1,* Yanqiu Fang1,2,* 1School of Chinese Medicine, Changchun University of Chinese Medicine, Changchun, People’s Republic of China; 2Center of Reproductive Medicine, Jilin Province People’s Hospital, Changchun, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaochun Feng, School of Chinese Medicine, Changchun University of Chinese Medicine, 1035 Boshuo Road, Changchun, 130117, People’s Republic of China, Email 18852099003@163.com Yanqiu Fang, School of Chinese Medicine, Changchun University of Chinese Medicine, 1035 Boshuo Road, Changchun, 130117, People’s Republic of China, Email yq.fang0920@163.comBackground and Purpose: Immunoglobulin A vasculitis (IgAV) is the most common systemic vasculitis of childhood. Zidian Zhenxiao granule (ZDZX), a 9-herb formula optimized through decades of clinical practice, uniquely integrates anti-inflammatory and immunomodulatory properties. However, its mechanisms targeting neutrophil extracellular traps (NETs) and thromboinflammatory pathways in combating IgAV remain unclear. This study aimed to investigate the main component of ZDZX and its underlying mechanism in IgAV treatment.Methods: Combining UHPLC-QE-MS/MS, network pharmacology, 4D-FastDIA proteomics, and a gliadin-induced IgAV murine model, we systematically deciphered ZDZX’s renoprotective and anti-inflammatory mechanisms.Results: 19 key components were identified in ZDZX, targeting 46 IgAV-associated proteins, predominantly enriched in TNF and IL-17 signaling pathways. In vivo, ZDZX significantly reduced levels of blood urea nitrogen (BUN) and creatinine (p < 0.01), attenuated renal IgA/C3 deposition, and improved hematological parameters. Proteomics revealed 27 differentially expressed proteins (DEPs) (FDR < 0.05), including MPO, IL-17, MMP2, C3 and COL1A1, implicating coagulation cascades and neutrophil extracellular trap (NET) formation. Additionally, ZDZX downregulated renal IL-6, TNF-α, and citrullinated histone H3 (CitH3) (p < 0.01), confirming NET inhibition, consistent with recent IgAV-NET mechanistic studies.Conclusion: By synergizing network pharmacology, 4D-FastDIA proteomics, and experimental validation, this study pioneers the demonstration that ZDZX alleviates IgAV via multi-target inhibition of NET-driven thromboinflammation.Keywords: anti-inflammatory, anti-NETs formation, immunoglobulin A vasculitis, network pharmacology, 4D-FastDIA proteomic, traditional Chinese medicine